(untitled) (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2026)
Jacket structures are three-dimensional steel framing systems that transfer top side loads to the foundation through legs, braces, and tubular joints. This study evaluates the linear-elastic response of a three-dimensional portal model representing a jacket leg system under vertical loading using SAP2000. The model consists of four legs connected by diagonal and horizontal braces, rigid joints, fixed base supports, and hollow circular sections. The analysis includes self-weight and four concentrated loads of 1 kN applied at the top. The revised study extends the original work through section-property calculations, load-path assessment, a unit-consistency audit, and a critical interpretation of the output contours. The SAP2000 displacement legends show an E-6 scale factor; assuming the model length unit is metre, the maximum Ux and Uy are 245×10⁻⁶ m or 0.245 mm, while Uz is 560×10⁻⁶ m or 0.560 mm. These values correct the initial metre-based interpretation. The reported axial response is compression-dominated, ranging from -1059.44 kN to +7.41 kN. The stress contour identifies the middle-brace region as a critical response zone; however, yielding cannot be concluded because the active stress unit was not documented. Reported torsion ranges from -4.60 to +3.42 kN·m, indicating internal coupling associated with the three-dimensional configuration. Linear static analysis is therefore useful for preliminary stiffness and load-path assessment, but unit verification, reaction equilibrium, member discretization, joint flexibility, soil-pile interaction, environmental loading, and nonlinear analysis are required before the model can support an offshore structural safety assessment.